High expression of Parkin predicts easier recurrence of patients with adjuvant transarterial chemoembolization. (October 2017) - Zhang, Changlie; Song, Zhihong; Yu, Guangji
Aim: To investigate the clinical significance of E3 ubiquitin ligase Parkin in patients with adjuvant transarterial chemoembolization after curative resection of hepatocellular carcinoma.Methods: Parkin expression of hepatocellular carcinomas was detected and its correlation with clinicopathological factors was analyzed with χ 2 test. The significance of Parkin in prognosis and recurrence was analyzed with log-rank test and the Cox-regression model.Results: High expression of Parkin could result in lower recurrence-free survival rate instead of overall survival rate. Larger tumor size, positive tumor recurrence, advanced T, N, M and TNM stage were significantly associated with poorer prognosis. Larger tumor size, advanced T and TNM stage could lead to higher recurrence.Conclusion: High Parkin expression could predict easier recurrence to patients with adjuvant transarterial chemoembolization.